OPTIMIZATION OF COMPUTER PROGRAM CODE: A MODEL APPROACH - Крихівський, Михайло; Бандура, Вікторія; Ваврик, Тетяна; Гобир, Лідія (SWorldJournal, 2024)
The work considers the optimization of the code of computer programs. Software code in today’s world is an integral part of various technologies, from mobile applications to large corporate systems. It is the basic building block of any program. Its perf